Postcolonial studies : a materialist critique - Parry, Benita (Postcolonial literatures., 2004)
Parry offers the compelling argument that theoretical work must strive to join remembrance of the material past with a critique of the contemporary condition, remaining unreconciled to the past and unconsoled by the present.